(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
Sars-Cov-2 pandemic has taken hold over the globe in the last months. Even the best healthcare systems all over the world are overwhelmed by the number of patients and the lack of personal protective equipment (PPE). Medical operators are exposed at high risk for contracting COVID-19. Additive manufacturing techniques allow to produce protective masks and facial shield. Thanks to 3D scans of the face, open-source files and software, many researchers and clinicians can print individualized PPE. This method paper aims to illustrate the key-aspects for producing individualized protective masks and face shields.